ANALYSIS OF FINANCIAL PERFORMANCE ISO 9000 CERTIFIED COMPANY (Empirical Study on the Manufacturing Companies Listed on the Stock Exchange) - Rini Oktaviana Sari (Universitas Trisakti, 2011)
Business competition in the era of globalization requires businesses to be more creative to produce a quality product to compete in the market International. ISO 9000 certification has been accepted as a reference for quality management and quality assurance. The purpose of this study was to determine differences in the performance of financial companies that have certified ISO 9000 as measured by levels of profitabiltas (ROCE, ROI, ROE), market growth (sales growth and growth equity) and management of liabilities (DTA and DER). This research method uses quantitative methods of research methods based on analysis of variables that can be explained quantitatively by using a formula that is by Financial Ratio Analysis.SimakBaca secara fonetik Technical analysisof the data in this research are descriptive analysis and statistics analysis. Statistical analysis to test data normality, if the normal data, using Paired Sample T-test and if the data is not normal, using the Wilcoxon Signed-rank Test. The conclusion from this research indicate that there is no difference whether the level of profitability, market growth and management of liabilities in the period before and after the certification of ISO 9000. No difference was attributable to that ISO certification is only for administrative completeness in order to obtain the logo of the certification institution, so as to indicate to consumers that its product quality.